Examining Gender Differences in the Relationship Between School Bonding and Opioid Misuse Among Justice-Involved Adolescents - Vroom, Enya B. (Journal of drug issues, 2023)
Justice-involved adolescents (JIAs) have an increased risk for opioid use disorder and overdose related to opioid misuse (OM). Consequences of untreated OM include recidivism and poor educational outcomes, which can be harsher for female JIA. Therefore, identifying relevant factors and settings that reduce the risk for OM is critical. Schools are a central institution in adolescent development. Drawing on social control theory, JIA with higher levels of school bonding was hypothesized to attenuate risk for OM. Cross-sectional data on 79,960 JIA from the Florida Department of Juvenile Justice were examined. Multivariate and stratified logistic regression analyses were employed. On average, for every one-unit increase in school bonding, JIA had 22%, female JIA had 23%, and male JIA had 22% lower odds of OM. Results suggest school bonding and the school context should be considered in treatment and how this setting may impact OM intervention outcomes among JIA.